2022
DOI: 10.1016/j.lfs.2022.120324
|View full text |Cite
|
Sign up to set email alerts
|

Renin-angiotensin system blockade on angiotensin-converting enzyme 2 and TMPRSS2 in human type II pneumocytes

Abstract: Aims Angiotensin-converting enzyme (ACE) 2 is the receptor for severe acute respiratory syndrome coronavirus 2 which causes coronavirus disease 2019 (COVID-19). Viral cellular entry requires ACE2 and transmembrane protease serine 2 (TMPRSS2). ACE inhibitors (ACEIs) or angiotensin (Ang) receptor blockers (ARBs) influence ACE2 in animals, though evidence in human lungs is lacking. We investigated ACE2 and TMPRSS2 in type II pneumocytes, the key cells that maintain lung homeostasis, in lung parenchym… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In agreement, sACE2 levels during COVID-19 did not differ depending on the presence of risk factors for severe COVID-19 infection (with the exception of male sex) and were not affected by RAS inhibition [29] . Accordingly, we have recently reported that ACEI/ARB treatment did not modify ACE2 protein expression in type II pneumocytes [12] which are key cells for lung homeostasis. In contrast, a report investigating ACE2 activity in plasma of hypertensive COVID-19 patients who were not experiencing severe COVID-19, found an increase in sACE2 activity under ACEI treatment compared to non-medicated COVID-19 people though with a smaller sample size (n = 9–10) [10] .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In agreement, sACE2 levels during COVID-19 did not differ depending on the presence of risk factors for severe COVID-19 infection (with the exception of male sex) and were not affected by RAS inhibition [29] . Accordingly, we have recently reported that ACEI/ARB treatment did not modify ACE2 protein expression in type II pneumocytes [12] which are key cells for lung homeostasis. In contrast, a report investigating ACE2 activity in plasma of hypertensive COVID-19 patients who were not experiencing severe COVID-19, found an increase in sACE2 activity under ACEI treatment compared to non-medicated COVID-19 people though with a smaller sample size (n = 9–10) [10] .…”
Section: Discussionmentioning
confidence: 92%
“…An increased sACE2 may reflect higher ACE2 expression, ACE2 shedding or both in those patients. However, we have recently shown that RAS blockade did not modify ACE2 protein expression in human type II pneumocytes, which are key cells for lung homeostasis, of subjects under ACEI treatment [12] . Here, we evaluated plasmatic sACE2 protein levels and enzymatic activity and Ang II and Ang-(1−7) levels in patients hospitalized with COVID-19 compared to healthy subjects.…”
Section: Introductionmentioning
confidence: 84%
“…Proteins in the supernatant were quantified. The supernatant was subsequently lyophilized and Ang extraction and recovery was performed as described elsewhere [28]. Each sample was corrected for each recovery.…”
Section: Cardiac Expression Of Ang II and Ang-(1-7)mentioning
confidence: 99%
“…Ang II level was quantified by radioimmunoassay using Anglabelled as described previously. Results were expressed as pg/mg tissue [28].…”
Section: Cardiac Expression Of Ang II and Ang-(1-7)mentioning
confidence: 99%
“…Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) may increase the expression of ACE2, resulting in concerns that patients with COVID-19 who are receiving these agents may be at increased risk of severe disease [5][6][7]. However, some recent studies concluded that ACEIs and ARBs do not modify the expression ACE2 and that they do not increase the replication of SARS-CoV-2 [8,9]. Moreover, contrary to the hypnotized negative effects of ACEIs and ARBs on COVID-19 patients, there are conflicting data that they might be beneficial.…”
Section: Introductionmentioning
confidence: 99%